2017
DOI: 10.1051/kmae/2016041
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and daily upstream movements of brown troutSalmo truttain an Iberian regulated river

Abstract: -Migrating fish are vulnerable to anthropogenic disturbances and, to assess the impact of human activities in freshwater ecosystems, it is vital to understand their movement patterns. The aim of this study is to describe the upstream movements of potamodromous brown trout Salmo trutta (seasonal and daily) and the potential environmental triggers in a regulated river in the northwest of the Iberian Peninsula (Porma River, León, Spain). Data collected in a fishway from October 2011 to January 2013 with a fish co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 27 publications
1
17
1
Order By: Relevance
“…Diurnal activity was frequent within the fishway and contrast with the supremacy of nocturnal spawning migrations of brown trout and barbel observed by Ovidio et al () and Baras, Lambert, and Philippart () in natural Belgian streams. A diurnal use of the fishway by brown trout was also observed by García‐Vega, Sanz‐Ronda, and Fuentes‐Pérez () in Spain. It is not excluded that trout natural migration rhythm change once in the fishway due to the artificial environment.…”
Section: Discussionsupporting
confidence: 69%
“…Diurnal activity was frequent within the fishway and contrast with the supremacy of nocturnal spawning migrations of brown trout and barbel observed by Ovidio et al () and Baras, Lambert, and Philippart () in natural Belgian streams. A diurnal use of the fishway by brown trout was also observed by García‐Vega, Sanz‐Ronda, and Fuentes‐Pérez () in Spain. It is not excluded that trout natural migration rhythm change once in the fishway due to the artificial environment.…”
Section: Discussionsupporting
confidence: 69%
“…We predict that (i) fish counts through the lift would vary between the different months for all three species following patterns outlined in the literature, i.e., cyprinid species movements should mainly occur during the reproductive season, i.e., summer [40,41], and further extending to early fall when species start to search for winter, feeding or thermal refuges [15,42] (with regard to the trout, movements are predicted as well to occur in the reproductive season, in this case, between late fall and early-winter [43]); (ii) daily activity of the studied species would not show marked diurnal/nocturnal preferences due to the absence of natural predators in the River Lima [16,44], which should not restrict movements to take place preferentially during the night, when survival is expected to be maximum [26]; (iii) water temperature and flow, two of the most important environmental factors responsible for triggering migration [35,45], would be the most significant ones for the target species; (iv) large-sized and faster-flowing species would be better able to cope with higher peak-flow magnitudes (50 and 100 m 3 s −1 ) than smaller ones, and hence expected to use the lift during such conditions; and (v) selectivity should be low, although the presence of larger individuals in the lift when compared to the downstream river segment, would be expected to occur as a result of upstream migration of adults to spawning sites [41].…”
Section: Introductionmentioning
confidence: 57%
“…Though some studies suggest that cyprinids are more active during the night to avoid predation (e.g., [37,41]), such patterns can be quite species-specific [16]. In a recent study conducted in the Meuse river basin (Belgium), Benitez et al [16] found that the common barbel Barbus barbus did not show any differences in daily activity when passing through the existing fishways, contrarily to the trout, which was more active during the day, a result that was also supported by some authors (e.g., [43]), but not others (e.g., [42]). In a series of surveys conducted in the Zêzere River (Tagus river basin), Santos et al [52] also did not find differences in daily activity for the Iberian straight-mouth nase (Pseudochondrosoma polylepis), a sister species of the present P. duriense.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Depending on the scale and dimensions of these structures, they can produce different impacts, e.g. fragmentation or loss of longitudinal connectivity (Lasne et al, 2007;Branco et al, 2012), geomorphological alterations (Graf, 2006) or, flow and thermal manipulations (García-Vega et al, 2017). Among all the possible consequences of cross-sectional structures, fragmentation of longitudinal connectivity is presumed to be one of the main ecological issues.…”
Section: Introduction Introduction River Regulation a Need With Consmentioning
confidence: 99%